Left Ventricular Outflow Tract Obstruction due to Primary Cardiac Tumors - Nantsios, Alex; Zapolanski, Alex; Grau, Juan; Jabagi, Habib (Archives of Clinical and Medical Case Reports, 2022)
Left Ventricular Outflow (LVOT) masses are rare and raise concern for infective endocarditis vegetations, thrombus, and cardiac tumors. When these masses arise in the LVOT, they can lead to symptoms of LVOT obstruction and thromboembolism. The most common cause of a cardiac tumor is cardiac myxoma, occurring in 0.02% of the population, and almost exclusively arises in the atria [1]. We present two cases of large cardiac masses of different pathology arising in the left ventricle causing LVOT obstruction.